Mechanisms for International Criminal Cooperation in Combating Money Laundering - Sura Hatim Majeed (المجلة الدولية للبحوث والدراسات القانونية, 2026)
This research examines the mechanisms of international criminal cooperation in combating the crime of money laundering as one of the most serious forms of transnational organized crime posing a direct threat to the economic and security stability of states. The study focuses on the international nature of money laundering and the international legislative framework established to combat it, particularly through the Vienna and Palermo Conventions, as well as the recommendations issued by the Financial Action Task Force (FATF).The research also addresses the principal forms of international criminal cooperation in combating money laundering crimes, including judicial delegation, extradition, enforcement of foreign criminal judgments, and controlled delivery operations, while clarifying the position of the Iraqi legislator under the Anti-Money Laundering and Counter-Terrorism Financing Law No. (39) of 2015.The study concludes that the effectiveness of combating money laundering depends largely on the efficiency of international cooperation and information exchange among states, in addition to the continuous development of domestic legislation in line with modern international standards aimed at confronting the evolving methods employed by organized criminal groups.